2015
DOI: 10.1007/s12070-015-0827-6
|View full text |Cite
|
Sign up to set email alerts
|

Importance of CT Scan of Paranasal Sinuses in the Evaluation of the Anatomical Findings in Patients Suffering from Sinonasal Polyposis

Abstract: Sinonasal polyps are benign lesions arising from nose and/or sinuses mucosa. Paranasal sinuses computed tomogram (CT) scan are important for functional endoscopic sinus surgery (FESS) as their information assist the surgeon in pre-operative planning. This study aimed to show importance of CT scan in evaluation of anatomical variations to prove a correlation with disease process and extent of disease in sinonasal polyposis patients. A study was done from Sept, 2010 to Sept, 2011 with 33 patients presenting with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 17 publications
0
13
1
Order By: Relevance
“…[9] This prevalence has been reported as between 21% and 75% in different studies. [7,[10][11][12][13][14][15] In our study, the prevalence of a nasal spur was 33.33% and nasal septal deviation was found in 69.04% of cases. The prevalence of nasal septal deviation in our study was very similar to that found in reports from other parts of Iran.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…[9] This prevalence has been reported as between 21% and 75% in different studies. [7,[10][11][12][13][14][15] In our study, the prevalence of a nasal spur was 33.33% and nasal septal deviation was found in 69.04% of cases. The prevalence of nasal septal deviation in our study was very similar to that found in reports from other parts of Iran.…”
Section: Discussionmentioning
confidence: 88%
“…The prevalence of concha bullosa in our study was 45.23%, while it has been reported to be between 9.09% and 61% in the literature. [7,[10][11][12]15,16] The reason for the apparently varying prevalence is that different definitions of the concha bullosa are in use. In studies reporting a higher prevalence, any air in the middle turbinate was considered concha bullosa, whilst in our study, only air in the bullous part of the middle turbinate was counted as concha bullosa.…”
Section: Discussionmentioning
confidence: 99%
“…They are usually bilateral with an appearance that is commonly bags-shaped, and have a characteristic semi-translucent appearance. 26,27 However, the diagnosis of patients with a unilateral mass should be based on radiographic imaging, possible biopsy, and careful follow-up. It is to be noted that chronic sinusitis such as mucoceles may also present with bone erosion, an expansile process, and low T 2 signal intensity due to the dehydration of retained secretions.…”
Section: Imaging Findings Of Paranasal Sinus Fibrosarcomamentioning
confidence: 99%
“…Since there are varied views with regarding to associations between sinonasal anatomical variants and rhinosinusitis in the literature this study was proposed. [18][19] The purpose of this study is to investigate the prevalence of sinonasal anatomic variants and to determine their relationship to chronic rhinosinusitis. Very few Indian studies are available for associations between anatomical variants and rhinosinusitis and this study also established the prevalence of sinonasal anatomical variants in suburban population of kancheepuram district, Tamilnadu.…”
Section: Introductionmentioning
confidence: 99%